Induction motor drive using seven level multilevel inverter for energy saving in variable torque load application - Pravin, S E; Starbell, R N (2011 International Conference on Computer, Communication and Electrical Technology, 2011)
The main objective of this paper is to control the speed of an induction motor by using seven level diode clamped multilevel inverter. To obtain high quality sinusoidal output voltage with reduced harmonics. The proposed Scheme for diode clamped multilevel inverter is multicarrier SPWM control. An open loop speed control can be achieved by using V/f method. This method can be implemented by changing the supply voltage and frequency applied to the three phase induction motor at constant ratio. The proposed system is an effective replacement for the conventional method which has high switching losses, as a result a poor drive performance. The simulation result portrays the effective control in the motor speed and an enhanced drive performance through reduction in total harmonic distortion (THD). The effectiveness of the system is verified through simulation using PSIM6.1 simulink package.